MERANCANG MODEL SIMULASI SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEMILIHAN CALON PEJABAT STRUKTURAL DI LINGKUNGAN UNIVERSITAS MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Sari Muliadi (JURNAL AKADEMIKA)
Decision Support System is a data processing system to be used as information to support decision-making of this semi-structured, and unstructured currently Analitycal method Hierarchy Process (AHP) is one way of decision support methods. Many examples of cases that can be used in decision support systems, such as the selection of election officials at the University of structural who had been executed by a team Baperjakat (Advisory Board Position and rank), because of some of the criteria and sub-criteria can be assessed as; Criteria Aspects of Psychology (section values psychology), work experience criteria, criteria values of leadership training, job performance criteria, presentations and interviews kriteri field of structural position. The end result of this is a decision support seistem posis determine structural position within the university based on the criteria being assessed.